Hexestrol Deteriorates Oocyte Quality via Perturbation of Mitochondrial Dynamics and Function - Niu, Dong; Chen, Kun-Lin; Wang, Yi; Li, Xiao-Qing; Liu, Lu; Ma, Xiang; Duan, Xing (Frontiers in Cell and Developmental Biology, 2021)
Hexestrol (HES) is a synthetic nonsteroidal estrogen that was widely used illegally to boost the growth rate in livestock production and aquaculture. HES can also be transferred to humans from treated animals as well as from the environment. HES has been showed to have a negative effect on ovarian function and oogenesis, but the potential mechanism has not been clearly defined. To understand the potential mechanisms regarding how HES affect female ovarian function, we assessed oocyte quality by examining the critical events during oocyte maturation. We found that HES has a negative effect on oocyte quality, indicated by the decreased capacity of oocyte maturation and early embryo development competency. Specifically, HES-exposed oocytes exhibited aberrant microtubule nucleation and spindle assembly, resulting in meiotic arrest. In addition, HES exposure disrupted mitochondrial distribution and the balance of mitochondrial fission and fusion, leading to aberrant mitochondrial membrane potential and accumulation of reactive oxygen species. Lastly, we found that HES exposure can increase cytosolic Ca2+ levels and induce DNA damage and early apoptosis. In summary, these results demonstrate that mitochondrial dysfunction and perturbation of normal mitochondrial fission and fusion dynamics could be major causes of reduced oocyte quality following HES exposure.